The Spatial and Temporal Characters of Demyelination and Remyelination in the Cuprizone Animal Model. Issue 11 (12th July 2019) - Zhang, Yanli; Cai, Lin; Fan, Kai; Fan, Bin; Li, Ning; Gao, Wenting; Yang, Xiaohan; Ma, Jianmei
ABSTRACT: Multiple sclerosis (MS) is the most common central nervous system disease due to demyelination in young adults, and currently, there is no cure. Some experimental animal models were generated to mimic specific aspects of MS pathological characteristics. Among them, the cuprizone (CPZ)‐induced mouse demyelination model presents heterogeneous pathologies with both focal and diffuse lesions. Considering that MS is a progressive disease, it is important to study the spatial and temporal characters of de‐ and remyelination in MS animal models. However, such data especially in some brain regions such as lateral septal area, fimbria of hippocampus, and hippocampus are still lacking. In this study, we investigated the alterations of myelin in these areas in parallel to the changes in corpus callosum using coronal sections. We found that the progression of demyelinating varied in different brain regions in C57BL/6J mice treated with CPZ for 1 to 5 weeks. This result suggests that each brain region has a distinct sensitivity to CPZ intoxication. Interestingly, activated microglia appeared not only in the active demyelinating areas but also in the non‐myelinolysis regions. After CPZ withdrawal, significant remyelination was started in corpus callosum as early as 3 days. The completion of remyelination in the entire brain regions took 3 weeks. Our study detailed characterized the dynamics of myelin alterations and microglial status in the brain of the CPZ model. This information is valuable to facilitate further MS studies utilizing the CPZ model. Anat Rec, 302:2020–2029, 2019. © 2019 American Association for Anatomy